If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6z + -18 = 9z + 12 Reorder the terms: -18 + -6z = 9z + 12 Reorder the terms: -18 + -6z = 12 + 9z Solving -18 + -6z = 12 + 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. -18 + -6z + -9z = 12 + 9z + -9z Combine like terms: -6z + -9z = -15z -18 + -15z = 12 + 9z + -9z Combine like terms: 9z + -9z = 0 -18 + -15z = 12 + 0 -18 + -15z = 12 Add '18' to each side of the equation. -18 + 18 + -15z = 12 + 18 Combine like terms: -18 + 18 = 0 0 + -15z = 12 + 18 -15z = 12 + 18 Combine like terms: 12 + 18 = 30 -15z = 30 Divide each side by '-15'. z = -2 Simplifying z = -2
| -15+n*2=13 | | 2(3x-2)=2(17x+14) | | 3x+15=8+x | | 5x+.6=1.8 | | 3w-2(.5w+1)=-4(2+w) | | -4x+1.1=-34.9 | | 28=t(r-4) | | 3/2-12x/5=-1/6 | | 19n+6+5-31=203 | | 11(9+3)=55 | | 5q^2-4pq-5q+4p=0 | | 2x+3(x-3)=6 | | 9(x-9)=8 | | -5(9)+2= | | 1-8z+24=-3z+1-7 | | 14-3*n=2 | | 0.2(0.1x+0.1)=-0.2 | | 7x+4.3-5.1x=0.3x-4.5 | | 2.25x+.14=.43x+.57 | | 2st^2+3s^2t-4st^2+14s^2t= | | 16-b^2=0 | | x^2-9x-3x-10=0 | | x^2-9x=3x-10 | | (4x^(2/3))-(19x^(1/3))-5=0 | | 2(8x+2)=50 | | .29x+.33=-.17x+.12 | | 22p+16=0.8986 | | -4.7x+1.9=-3.1x+2.3 | | 10+n*3=55 | | .29+.33=-.17+.12 | | (2x+4)+(3x-29)=180 | | 10+n*3=46 |